2011
DOI: 10.1590/s0100-879x2010007500152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 174 G/C polymorphism in the promoter region of the interleukin-6 gene on plasma IL-6 levels and muscle strength in elderly women

Abstract: We investigated the effect of -174 G/C single-nucleotide polymorphism in the promoter region of the IL6 gene on plasma IL-6 levels and muscle strength, and the relationship between IL-6 levels and muscle strength in elderly women. The sample consisted of 199 elderly residents (73.0 ± 7.8 years old) from rest homes and the community in Belo Horizonte, MG, Brazil. -174 G/C polymorphism was determined by direct sequencing of the product by PCR, and plasma IL-6 concentrations were measured by ELISA. Muscle strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 40 publications
1
27
0
2
Order By: Relevance
“…Because of the necessary precondition, phenotypic manifestation of rs1800795 is not universal. For instance, impact of rs1800795 (in terms of association with increased IL-6 levels) has been found in inflammation-related conditions such as ageing [15], systemic-onset juvenile chronic arthritis [14], liver cirrhosis, hepatocellular carcinoma [16], primary Sjogren's syndrome [17] as well as in medicated schizophrenia patients [8]. However, lack of this association [18] or even reversal of such association [19] has been reported in healthy individuals, which possibly reflects absence of environmental triggers of transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the necessary precondition, phenotypic manifestation of rs1800795 is not universal. For instance, impact of rs1800795 (in terms of association with increased IL-6 levels) has been found in inflammation-related conditions such as ageing [15], systemic-onset juvenile chronic arthritis [14], liver cirrhosis, hepatocellular carcinoma [16], primary Sjogren's syndrome [17] as well as in medicated schizophrenia patients [8]. However, lack of this association [18] or even reversal of such association [19] has been reported in healthy individuals, which possibly reflects absence of environmental triggers of transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these studies, -174G>C has the highest impact on transcription regulation, making it a functional polymorphism (Falleti et al, 2010). Homozygotes for the G allele have been shown to have higher plasma levels of IL-6, higher IL-6 gene transcription activity and higher inducible IL-6 responses compared to subjects homozygous for the C allele (Pereira et al, 2011). In spite of the evidence supporting a positive association between -174G allele and higher IL-6 levels, studies have shown that it is the C allele that is associated with prostate cancer (Terry et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…4 Single-nucleotide polymorphisms (SNPs) identified in the promoter regions of the IL-6 gene have been shown to influence mRNA and IL-6 levels in the circulation and are implicated in the development and progression of inflammatory conditions. [5][6][7] The IL-6 SNP at position 174 in the promoter region is of particular importance in chronic inflammatory diseases. 8 The IL-6 gene is located at chromosome 7 position p21, 9,10 whereas the IL-6 -174 SNP is situated near a transcription factor ''hotspot area'' that is closely related to transcriptional 1 regulation of IL-6.…”
Section: Introductionmentioning
confidence: 99%